2003
DOI: 10.1002/cncr.11867
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II trial of suramin monthly × 3 for hormone‐refractory prostate carcinoma

Abstract: BACKGROUND The goal of the current study was to determine the prostate‐specific antigen (PSA) and objective response rates and the pharmacokinetics associated with a monthly × 3 one‐hour infusion of suramin in 58 patients with hormone‐refractory prostate carcinoma. METHODS A PSA response was defined as a > 50% reduction in the PSA level from baseline for at least 3 consecutive evaluations over a minimum of 6 weeks. The suramin dose was 2400 mg/m2 taken intravenously on Day 1, 1620 mg/m2 on Day 29, and 1292 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…29,30 Suramin has been used to treat prostate and breast cancers in clinical settings. 31,32 Recent experimental studies showed that it is also effective in attenuating muscle and liver fibrosis. 33,34 However, it remains unclear whether suramin has an antifibrotic effect in the kidney.…”
mentioning
confidence: 99%
“…29,30 Suramin has been used to treat prostate and breast cancers in clinical settings. 31,32 Recent experimental studies showed that it is also effective in attenuating muscle and liver fibrosis. 33,34 However, it remains unclear whether suramin has an antifibrotic effect in the kidney.…”
mentioning
confidence: 99%
“…It is in clinical trials for some metastatic cancers such as renal, prostate carcinomas and lymphomas, but has not been considerably successful because of its broad spectrum of toxicity. 17,18 Therefore current studies use suramin in low concentrations as a sensitizer or to reverse b FGFinduced chemoresistance.…”
mentioning
confidence: 99%
“…It is in clinical trials for some metastatic cancers such as renal, prostate carcinomas and lymphomas, but has not been considerably successful because of its broad spectrum of toxicity. 17,18 Therefore current studies use suramin in low concentrations as a sensitizer or to reverse b FGFinduced chemoresistance. 19 Many preclinical and clinical trials are also being carried out where suramin is being combined with other compounds to reduce its effective concentration and overall toxicity.…”
mentioning
confidence: 99%
“…More importantly, suramin is currently being pursued for the treatment of many cancers as a single agent and in combination therapy with many anti-cancer chemotherapeutic agents including cisplatin (56)(57)(58)(59). Our data also indicate that suramin does not inhibit cisplatin's cytotoxic efficacy.…”
Section: Figure 1 Pretreatment With High Dose Suramin Improves Markesupporting
confidence: 57%